Severe Fever With Thrombocytopenia Syndrome in Southeastern China, 2011–2019 - Tao, Mingyong; Liu, Ying; Ling, Feng; Chen, Yijuan; Zhang, Rong; Ren, Jiangping; Shi, Xuguang; Guo, Song; Lu, Ye; Sun, Jimin; Jiang, Jianmin (Frontiers in Public Health, 2022)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease and the number of cases has increased in recent years in Zhejiang Province, China. We want to explore whether the seasonal distribution, geographic distribution and demographic characteristics of SFTS have changed with the increase of incidence. Materials and Methods: The data on SFTS cases in Zhejiang Province from 2011 to 2019 were collected. Descriptive method was used to analyze the changing demographic characteristics and seasonal distribution. Global Moran’s I was used to explore the spatial pattern; local indicator of spatial association was depicted by Local Getis-Ord statistic; Spatial scan statistic was used to monitor the space-time clusters. Results: A total of 463 SFTS cases including 53 (11.45%) deaths were reported from 2011 to 2019 and the annual number of cases showed increase tendency. SFTS cases were reported in almost half of the counties (40/89) of Zhejiang Province. The elderly farmers were most infected and over time the proportion of farmer has increased. About 376 cases (81.21%) were reported during April and August. The interval from illness onset to confirmation of SFTS cases showed a lowering trend (Z= 5.194, P< 0.001). The majority of cases were reported in Zhoushan City from 2011 to 2016, but most SFTS cases were reported in Taizhou City since 2017. Discussion: SFTS was widely spread in Zhejiang Province and some characteristics have changed. Comprehensive intervention measures including clearance of breeding sites, killing of tick adults, health education should be strengthened in farmers of the key areas according to the changed epidemiological characteristics.